2021
DOI: 10.3390/pathogens10111441
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Antibody Transfer of Respiratory Syncytial Virus Specific IgG in Non-Human Primate Mother-Infant Pairs

Abstract: One approach to protect new-borns against respiratory syncytial virus (RSV) is to vaccinate pregnant women in the last trimester of pregnancy. The boosting of circulating antibodies which can be transferred to the foetus would offer immune protection against the virus and ultimately the disease. Since non-human primates (NHPs) have similar reproductive anatomy, physiology, and antibody architecture and kinetics to humans, we utilized this preclinical species to evaluate maternal immunization (MI) using an RSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 127 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…Similarly, the F-based RSV vaccine was shown to be immunogenic to ameliorate antibody levels in recipients, including non-pregnant healthy women [24] and specific populations, e.g., the elderly and children [25]. A growing body of research in vivo also demonstrated how passive immunization of the offspring by administering F-based RSV jab to the dams is helpful to promote MatAbs, in both the dams and their offspring [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the F-based RSV vaccine was shown to be immunogenic to ameliorate antibody levels in recipients, including non-pregnant healthy women [24] and specific populations, e.g., the elderly and children [25]. A growing body of research in vivo also demonstrated how passive immunization of the offspring by administering F-based RSV jab to the dams is helpful to promote MatAbs, in both the dams and their offspring [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of maternal antibodies protects against most severe RSV infection during the first weeks after birth. Passive immunity via transplacental antibodies is critically dependent on gestational age at delivery with little transfer in children born before 28-32 weeks of gestation 94 .…”
Section: Immune Responsementioning
confidence: 99%